LEARNING ARABIC WRITING SKILL BASED ON DIGITAL PRODUCTS - Mufidah, Nuril; Suryawati, Dessy; Bin Tahir, Saidna Zulfiqar; Sa’adah, Nihayatus (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
The development of technology can be used as a means of supporting learning. Like learning based on digital products for students.Â The study aimed at describing and analyzing the implementation of learning Arabic Writing Skill (Maharah Kitabah) based on digital products, namely the creation and publication of journal articles and its effects on the learning process. This research was conducted on 22 students writing skills class (Maharah Kitabah) 3, 5th of the semester. The method in this research is descriptive qualitative. Data collection techniques are, 1) observation of learning writing skills (Maharah Kitabah) III, 2) interviews with lecturers and students writing skills classes (Maharah Kitabah) III about the implementation of Arabic Writing Skill (Maharah Kitabah)based on digital product and the impact, and 3) documentation of learning data and works student digital products. Maharah Kitabah learning based on digital products in the form of writing scientific articles online by utilizing references and references of digital managers has a good impact for the students who took part in the Maharah Kitabah learning process with this model, all students were able to make Arabic journal articles using Mendeley and Turnitin citations, and students were able to publish Arabic journal articles to national e-journals.